Temperature dependence of liquid lithium film formation and deuterium retention on hot W samples studied by LID-QMS. Implications for future fusion reactors. (7th February 2018) - de Castro, A.; Sepetys, A.; González, M.; Tabarés, F.L.
Abstract: Liquid metal (LM) divertor concepts explore an alternative solution to the challenging power/particle exhaust issues in future magnetic fusion reactors. Among them, lithium (Li) is the most promising material. Its use has shown important advantages in terms of improved H-mode plasma confinement and heat handling capabilities. In such scenario, a possible combination of tungsten (W) on the first wall and liquid Li on the divertor could be an acceptable solution, but several issues related to material compatibility remain open. In particular, the co-deposition of Li and hydrogen isotopes on W components could increase the associated tritium retention and represent a safety risk, especially if these co-deposits can uncontrollably grow in remote/plasma shadowed zones of the first wall. In this work, the retention of Li and deuterium (D) on tungsten at different surface temperature (200 °C–400 °C) has been studied by exposing W samples to Li evaporation under several D2 gaseous environments. Deuterium retention in the W–Li films has been quantified by using laser induced desorption-mass spectrometry (LID-QMS). Additional techniques as thermal desorption spectroscopy, secondary ion mass spectrometry, profilemetry and flame atomic emission spectroscopy were implemented to corroborate the retention results and for the qualitative and quantitative characterization of the films. The results showed a negligible (below LID sensibility) D uptake at T surface   =  225 °C, when the W–Li layer is exposed to simultaneous Li evaporation and D2 gas exposition (0.67 Pa). Pre-lithiated samples were also exposed to higher D2 pressures (133.3 Pa) at different temperatures (200 °C–400 °C). A non-linear drastic reduction in the D retention with increasing temperatures was found on the W–Li films, presenting a D/Li atomic ratio at 400 °C lower than 0.1 at.% on a thin film of  ≈100 nm thick. These results bode well (in terms of tritium inventory) for the potential utilization of this material combination in a real reactor scenario.